Study and production of thin-film memristors based on TiO2 – TiOx layers; IOP Conference Series: Materials Science and Engineering; Vol. 498 : Advanced Micro- and Nanoelectronic Systems and Technologies - Zhidik E. V. Ekaterina Vyacheslavovna; Troyan P. E. Pavel Efimovich; Sakharov Yu. V. Yury Vladimirovich; Zhidik Yu. S. Yury Sergeevich; Korzhenko D. V. Dmitry Vladimirovich (2019, 2019)
Title screen